2009
DOI: 10.1016/j.ceca.2009.07.008
|View full text |Cite
|
Sign up to set email alerts
|

TRPC1 inhibits apoptotic cell degeneration induced by dopaminergic neurotoxin MPTP/MPP+

Abstract: Disturbances in Ca2+ homeostasis have been implicated in a variety of neuropathological conditions including Parkinson’s disease (PD). However, the importance of store-operated Ca2+ entry (SOCE) channels in PD remains to be investigated. In the present study, we have scrutinized the significance of TRPC1 in 1-methyl- 4-phenyl-1, 2, 3, 6 -tetrahyrdro-pyridine (MPTP)-induced PD using C57BL/6 animal model or PC12 cell culture model. Both sub-acute and sub-chronic treatments of MPTP significantly reduced TRPC1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 49 publications
10
87
0
1
Order By: Relevance
“…In particular, recent studies have shed light on the neuroprotective effect of TRPC channels in the SNpc against Tat neurotoxicity (49). Our previous studies also show the neuroprotective action of TRPC1 against in vitro cell culture models of PD (19); however, the precise mechanisms by which TRPC1 regulates neuronal survival remained poorly understood. In this study, we showed that TRPC1 overexpression confers protection against ER stress in both in vivo and in vitro models of PD.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In particular, recent studies have shed light on the neuroprotective effect of TRPC channels in the SNpc against Tat neurotoxicity (49). Our previous studies also show the neuroprotective action of TRPC1 against in vitro cell culture models of PD (19); however, the precise mechanisms by which TRPC1 regulates neuronal survival remained poorly understood. In this study, we showed that TRPC1 overexpression confers protection against ER stress in both in vivo and in vitro models of PD.…”
Section: Discussionmentioning
confidence: 94%
“…Proteins were resolved in 4%-12% NuPAGE gels, followed by Western blotting with the desired antibodies. Crude membrane or lysates were prepared from SH-SY5Y cells and from animal and human tissues as previously described (18,19). Protein concentrations were determined using the Bradford reagent (Bio-Rad), and 25-50 μg of lysates were resolved on NuPAGE 4%-12% Bis-Tris gel or NuPAGE 3%-8% Tris-acetate gels (Invitrogen), followed by Western blotting as described in refs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TRP channels are expressed in tumours [62]. Ca 2þ entry through TRP channels may inhibit apoptosis [63,64], an effect partially attributed to the stimulation of NF-kB [64]. Moreover, TRPP2 channels may, by an increase in the endoplasmatic reticulum Ca 2þ permeability, deplete Ca 2þ stores thus blunting the intracellular Ca 2þ release upon apoptotic stimuli [4,65].…”
Section: Ca 2þ Permeable Cation Channelsmentioning
confidence: 99%
“…MPTP is a potent neurotoxin that selectively destroys the nigrostriatal dopaminergic neurons in humans, sub-human primates, and lower animals [12][13][14]. MPTP is a highly lipophilic compound and can cross the blood brain barrier [15].…”
Section: Introductionmentioning
confidence: 99%